2022
DOI: 10.1017/s0033291722001519
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of suicidal behaviours in a representative epidemiological youth sample in Hong Kong: the significance of suicide-related rumination, family functioning, and ongoing population-level stressors

Abstract: Background Young people are most vulnerable to suicidal behaviours but least likely to seek help. A more elaborate study of the intrinsic and extrinsic correlates of suicidal ideation and behaviours particularly amid ongoing population-level stressors and the identification of less stigmatising markers in representative youth populations is essential. Methods Participants (n = 2540, aged 15–25) were consecutively recruited from an ongoing large-scale household-based epidemiological youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…While influences of social unrest and the COVID-19 on mental health have already been reported in prior work, 2 , 3 , 4 , 12 our study provided additional information concerning their additive influences on mental health in a representative epidemiological youth sample with consideration of a wide range of personal and environmental factors. By segregating our analyses into four periods, we showed that the prevalence of disorders and their risk factors could be subject to large-scale environmental changes.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…While influences of social unrest and the COVID-19 on mental health have already been reported in prior work, 2 , 3 , 4 , 12 our study provided additional information concerning their additive influences on mental health in a representative epidemiological youth sample with consideration of a wide range of personal and environmental factors. By segregating our analyses into four periods, we showed that the prevalence of disorders and their risk factors could be subject to large-scale environmental changes.…”
Section: Discussionmentioning
confidence: 68%
“… 18 , 19 , 20 As in the study showing increased youth suicide rate in Japan during COVID-19, 37 our previous work has also shown that both personal factors and COVID-19 stressors can contribute to suicidal ideation and attempts in the local youth population. 2 The epidemiology of mental disorders thus requires consideration of the complex interactions between individual vulnerabilities, personal risk factors, and ongoing changes at the population level. 3 , 9 , 40 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the HK-YES have been reported elsewhere. [18][19][20][21][22][23] Written informed consent was obtained from all participants, with consent obtained from parents or legal guardians for those below the age of 18. The authors assert that all procedures contributing to this work comply with the ethical standards of the relevant national and institutional committees on human experimentation and with the Helsinki Declaration of 1975, as revised in 2008.…”
Section: Participantsmentioning
confidence: 99%